MAP3Kinase-dependent SnRK2-kinase activation is required for abscisic acid signal transduction and rapid osmotic stress response - Yohei Takahashi (Nature Portfolio, 2020)
SnRK2 kinases activate abiotic stress responses in plants following ABA-dependent phosphatase inhibition or ABA-independent osmotic stress signalling. Here Takahashi et al. show that MAPKK-kinases phosphorylate and activate SnRK2s thus enabling robust ABA and osmotic stress signal transduction.